The Validity of Unilateral Termination of Insurance Contracts After the Constitutional Court Decision No. 83/PUU-XXII/2024: : A Study on Jasindo Insurance - Nurul Aulia; Zeehan Fuad Attamimi; Mahira Korai; Zanele Manhica (Fakultas Hukum Universitas Djuanda, 2026)
This study examines the intersection of insurance contract law, consumer protection policy, and regulatory compliance in the financial sector. It aims to analyze the implementation of Constitutional Court Decision No. 83/PUU-XXII/2024 in limiting the right of unilateral termination of insurance contracts, as well as the strategies adopted by Jasindo Insurance in mitigating post-decision conflict risks. This topic is selected due to the significance of the decision in reforming insurance law, the urgency of conflict mitigation within Jasindo as a state-owned enterprise, and the existing gap in the literature regarding its implementation. This research employs a normative juridical method with a qualitative approach, combining the analysis of primary legal materials, including the Constitutional Court decision, with field data obtained through interviews to assess its application within Jasindo Insurance. The findings indicate that the decision has enhanced legal certainty for consumers; however, its implementation within Jasindo faces challenges due to inconsistencies between the ruling and existing business practices. The study reveals that implementation remains suboptimal due to discrepancies in policy clauses, potential disputes, and the need for compliance-based adaptive strategies. This research contributes to the development of insurance law by offering theoretical and practical recommendations to balance consumer protection and business compliance, while emphasizing the importance of a solution-oriented framework for effective implementation within Jasindo Insurance.